The art of marriage : a guide for living life as two - Blyth, Catherine (Gotham Books, 2011)
An argument in support of marriage draws on historical anecdotes and modern research as well as the insights of couples to share counsel on topics ranging from infidelity and intimacy to conflicts and the views of leading skeptics.